Gastric duplication cyst: rare cause of upper gastrointestinal bleeding in a young adult, with a review of literature - Loong, Philip Ding Hsin; Fan, Ling Li; Ramasamy, Umasangar (International Surgery Journal, 2021)
Duplication cyst along the alimentary canal is a congenital anomaly which is rare and usually incidentally found at endoscopy or radiological imaging. It can develop anywhere along the alimentary canal with only 4% occurrence in the stomach. Only few cases of gastric duplication cysts were reported to be symptomatic along with its complications. Diagnostic modalities include oesophageo-gastroduodenoscopy (OGDS), endoscopic ultrasound (EUS), computerized tomography (CT) scan and magnetic resonance imaging (MRI). However, the best option to confirm the diagnosis is complete resection of the lesion. We are reporting about a teenage girl whereby she presented with sudden episodes of hematemesis, which led to a syncopal attack. She also complained of intermittent central abdominal pain for a month prior to her presentation. Physical examination was unremarkable. However, her blood investigation showed a significant drop in hemoglobin. The patient had an endoscopy during which a submucosal lesion at the greater curvature was identified and the provisional diagnosis we had was a gastrointestinal stromal tumor (GIST). CT scan of the abdomen was also done showing an endoluminal cystic gastric lesion measuring approximately 2×2×2 cm. The lesion was confined to the stomach with no local infiltration of the adjacent structures. Decision was made to proceed with a laparoscopic wedge resection after outweighing the risk and benefits of surgery. Gastric duplication cyst is a rare anomaly. Despite its rarity, it should be included as a differential when we encounter a submucosal lesion due to its tendency for malignant transformation and other complications.